Pengembangan Buku Digital Berbasis Multiple Representasi Pada Materi Ikatan Kimia Sebagai Sumber Belajar Berbasis Digital Siswa SMA Kelas X - Rumondor, Desire; Akbar, Jakub Saddam; Howan, Dian Herlinda Octorina; Djakariah, Djakariah; Akbar, Ayu Febrianty (Oxygenius: Journal Of Chemistry Education, 2025)
This study aims to develop a digital textbook based on multiple representations on chemical bonding as a digital learning resource for 10th-grade high school students. Product development was conducted using the Research and Development (R&D) method with the ADDIE model. Product validation involved media experts, material experts, and field trials with students using a Likert scale questionnaire instrument of 1–5. The assessment results showed that the digital textbook received a "Very Good" category from media experts (86.23%), material experts (85.20%), and student responses (94.35%). This digital textbook integrates three levels of chemical representation: macroscopic (real phenomena), microscopic (particle structures), and symbolic (chemical equations) through interactive features such as molecular animations, simulations, explanatory videos, and evaluation quizzes. The product meets the standards of the Independent Curriculum, has an intuitive user interface, and can be accessed across multiple devices. In conclusion, this digital textbook based on multiple representations is suitable for use as a digital learning resource for 10th-grade high school students on chemical bonding.